1990
DOI: 10.1136/jech.44.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy: social class differences in prevalence in relation to birthweight and severity of disability.

Abstract: Study objective-The aim of the study was to examine the possible influence of social class on the prevalence of cerebral palsy.Design-The study was a retrospective population based survey of all cases of cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
54
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 7 publications
6
54
0
4
Order By: Relevance
“…Multiple birth is one changing risk factor, increasing during the study period because of increasing maternal age and use of assisted conception, but multiple births at low gestational age are not at a substantially greater or lower risk of CP than singletons of the same gestational age (Topp et al 2004). Previous studies have found no socioeconomic gradient for CP among low birthweight births (Dowding andBarry 1990, Dolk et al 2001), so it is unlikely that socioeconomicallyrelated risk factors, such as maternal smoking, have a strong positive or negative association with risk of CP, independent of their effect on birthweight.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Multiple birth is one changing risk factor, increasing during the study period because of increasing maternal age and use of assisted conception, but multiple births at low gestational age are not at a substantially greater or lower risk of CP than singletons of the same gestational age (Topp et al 2004). Previous studies have found no socioeconomic gradient for CP among low birthweight births (Dowding andBarry 1990, Dolk et al 2001), so it is unlikely that socioeconomicallyrelated risk factors, such as maternal smoking, have a strong positive or negative association with risk of CP, independent of their effect on birthweight.…”
Section: Discussionmentioning
confidence: 95%
“…Aetiology of most cases is unclear, although observations of socioeconomic gradients in prevalence (Dowding andBarry 1990, Dolk et al 2001) suggest environmental factors may be important. Magnetic resonance imaging studies indicate that of individuals with CP born at term, the aetiology of CP may be of late third trimester origin in a third, of early third trimester origin in a third, and of earlier or genetic origin associated with brain malformations in another third (Krageloh-Mann 2000) of those affected.…”
mentioning
confidence: 99%
“…Previous studies using measures of SES based on parental occupation [13][14][15][16][17] or an area based measure of SES 18 19 have produced conflicting results (table 1). In some studies the apparent lack of an association with lower SES may be related to study methodology.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborates the study by Halpern et al (7) , which found that children from low SES families were twice as likely to present a delay in their neurodevelopment compared to those with higher SES. A study by Dowding and Barry (28) , proved that the social class affected the most severe cases of CP.…”
Section: Discussionmentioning
confidence: 99%